The Russian Bible Society and the Russian Orthodox Church - Zacek, Judith Cohen (Church history, 1966)
The historian Presniakov has characterized the first quarter of the nineteenth century, the reign of Alexander I, as “Russia at the crossroads” (Rossiia na rasput'i). No longer content with slavish imitation of Western Europe, Russia now began to develop a culture which would be admired and emulated by the West. Once beyond the fringe of European diplomacy, the Empire now moved to the center of that arena. Shaped by her national traditions, but involved increasingly in continent-wide trends, the Russia of Alexander I was confronted by a varied and complex set of problems, both domestic and foreign, which demanded resolution. The destruction of the Napoleonic threat, the assimilation of subject nationalities, the establishment of efficient techniques and procedures of government, the articulation and implementation of national policies in education and in economic life were among the countless tasks which faced Alexander I and his advisors. Educated Russians of the day heatedly debated the most effective means of solving the myriad dilemmas.